The Guidelines of Self Improvement for Employees to be Professionals and Create Competitive Adventage of Electrical Indiusty in Rayong Province - แสงเพชร, พีรพันธ์ (Journal of Industrial Business Administration, 2019)
The objective of this research is to study The Guidelines of Self Improvement for Employees to be Professionals and Create Competitive Advantage of Electrical Industry in Rayong Province. Classified by personal factor such as genders, age, marriage status, education, year of service and income. The sample size is 100 people. This study use questionnaire. The statistical tools are Percentages, Mean, Standard Deviation, t-test, Anova and Scheffe Analysis. SPSS is used for data analysis at a statistical level of .05. The research results indicate that majority of employee who work in Electrical Industry are male age between 25-35 years old. Single and hold a bachelor’s degree. The year of service is more than 10 years in Operator level. Average income range is 20,000 - 40,000 THB. In conclusion, the employees who work in the Electrical Industry in Rayong Province have high level of priority in the guidelines of self improvement. The analysis of different between the level of priority and age exhibits that there are differences in overall overview and six differences in term of the Learning, Self-Diagnosis, Goal, Finding Appropriate Resources, Strick ability and Perseverance and Evaluation. And the analysis of difference between age, marriage status, education, year of service and income and level of priority are no difference.